Effects of integrated interventions on growth and development of young children: A meta-analysis. (30th September 2020) - Dulal, S; Prost, A; Saville, N; Karki, S; Merom, D
Abstract: Background: We did a systematic review to understand: (a) the effects of integrated versus usual care on the developmental outcomes and nutritional status of children under five years; and (b) which intervention characteristics are associated with positive effects. Methods: We searched eight electronic databases for studies published between January 2013 and September 2019. Eligible studies were Randomised Controlled Trials (RCTs) and non-randomised controlled studies of integrated nutrition and stimulation interventions with child growth and developmental outcomes. We extracted data on intervention characteristics including delivery strategies, behaviour change techniques, intervention intensity and delivery personnel. We meta-analysed data for Length-for-age/Height-for-age Z scores (LAZ/HAZ) and cognitive, motor and language development scores, and conducted subgroup analyses by main intervention characteristics. Results: Twenty-two unique RCTs met the inclusion criteria, of which 16 were included in the meta-analysis. Compared to the usual care, pooled Effect Sizes (ES) showed small to medium benefits of integrated interventions on cognitive (n = 15, ES 0.64; 95% CI: 0.39, 0.88) and language development scores (n = 10, ES 0.47, 95% CI: 0.21, 0.73) but heterogeneity was high (I2>75%). We found no significant effects of interventions on motor development scores (n = 12, ES 0.31, 95% CI: -0.02, 0.64) or LAZ/HAZ scores (n = 8, ES -0.03, 95% CI: -0.11, 0.03). The effects of interventions on developmental outcomes did not differ by intervention characteristics, and heterogeneity remained high in sub-group analyses. Conclusions: Integrated nutrition and stimulation interventions had significant effects on cognitive and language development, but no detectable effect on motor development or linear growth. Our ability to identify intervention characteristics linked to positive effects can be improved by standardising the reporting of implementation processes. Key messages: More high-quality trials with longer follow-up duration are needed to examine the role of integrated nutrition and stimulation interventions on growth and developmental outcomes. Future research should map the characteristics of integrated nutrition and stimulation interventions following standardised guidelines to understand their influence on the outcomes reported.